Spillovers in State Capacity Building: Evidence from the Digitization of Land Records in Pakistan - Aman-Rana, Shan; Minaudier, Clement (American Economic Review, 2026)
Digitization reforms have been hailed as an effective way of strengthening state capacity. However, digitization can also fundamentally reshape the organization of bureaucracies. Using a unique administrative dataset on agricultural taxation and surveys of local bureaucrats from Punjab, Pakistan, we show that digitization reforms can have unintended consequences for state capacity. We exploit the staggered rollout of the digitization of land records in Punjab to show that digitization had a negative effect on tax collection. The fall in taxes was not due to a decrease in the tax base. Instead, digitization affected the bureaucrats’ capacity to collect taxes. (JEL D73, H11, H71, O12, O17)